Dampak Penggunaan Gadget dalam Pembelajaran pada Siswa Sekolah Dasar - Sari, Poppy Amelia Sari; Puspitasari , Juniar Dwi Puspitasari; Widiastuti, Tika Anggun (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The use of gadget technology in elementary school students' learning has a big impact on the teaching and learning process. This study aims to find out the impact of using gadget technology in learning for elementary school students. This research uses qualitative methods with data collection techniques through library research. In this research, data is taken from sources such as books, articles and research that has been carried out previously related to this material. The data analysis technique used in this research is a descriptive method by describing and interpreting what exists. The use of gadgets can increase children's creativity if used wisely. Considering the greater negative impact of gadget use on elementary school children, it is important to find solutions on how to divert children from becoming addicted to gadgets. One solution is to encourage children to interact outside the home more often, such as playing outside or playing with peers of the same age. Apart from that, giving educational toys to children can also reduce addiction to these gadgets. The solution to reducing gadget use is through external learning based on local wisdom and traditional games. This activity is to form an agent for driving old games to reduce the use of gadgets among elementary school students. The use of gadgets can give negative and positive impressions to students